The Directive 2006/24 declaration of invalidity and the consequences of metadata retention in the EU Member States: A Fundamental Rights Standards Approach - Silveira, Alessandra; Freitas, Pedro Miguel (Law, State and Telecommunications Review, 2017)
Purpose ”“ The text deals with the recent case law of the European Court of Justice (ECJ) on the directive on the retention of data (metadata) by providers of electronic communications services for the purposes of investigation, detection and prosecution of serious crimes. The authors seek to clarify the implications of the declaration of invalidity of this European directive for the EU Member States, towards the protection of legal equality of European citizens. Methodology/approach/design ”“ The text was drafted while there was a pending ECJ’s response to the questions referred by two national courts (one Swedish and one British) on the effects of that invalidity decision on the domestic legislation that transposed it. Thus, the authors sought to anticipate the Court’s decision in the light of its settled case law and the reaction of the Member States’ authorities’ after the declaration of invalidity of the referred directive. Findings ”“ In the light of the particularities of the protection of fundamental rights in the EU and the legal model of integration, the authors draw some guidelines as to the procedure to be followed in future cases in order to safeguard the effectiveness of the Union law, namely when it comes to the legal equality of European citizens.